2004
DOI: 10.1093/pcp/pch040
|View full text |Cite
|
Sign up to set email alerts
|

Two GLOBOSA-Like Genes are Expressed in Second and Third Whorls of Homochlamydeous Flowers in Asparagus officinalis L.

Abstract: Garden asparagus (Asparagus officinalis L.) has homochlamydeous flowers. Like Liliaceae plants such as lily and tulip, the perianths of asparagus have two whorls of almost identical petaloid organs, called tepals. Floral structures of these homochlamydeous flowers could be explained by a modified ABC model, in which the expression of the class B genes has expanded to whorl 1, so that the organs of whorls 1 and 2 have the same petaloid structure. In this study, we isolated and characterized two GLOBOSA-like gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…The expression patterns of paleoAP3/TM6-and PI-lineage genes in asparagus (Asparagus officinalis; AODEF and AOGLOA/B, respectively) are not in agreement with the modified ABC model because these genes are expressed only in whorls 2 and 3 and not in whorl 1 ( Fig. 3F; Park et al, 2003Park et al, , 2004. However, an asparagus floral homeotic mutant with two whorls of sepaloid tepals in whorls 1 and 2 and stamens transformed to carpels in whorl 3 has been identified ( Fig.…”
Section: -2) Lily-type Flowers-a Perianth With Two Petaloid Whorlsmentioning
confidence: 99%
“…The expression patterns of paleoAP3/TM6-and PI-lineage genes in asparagus (Asparagus officinalis; AODEF and AOGLOA/B, respectively) are not in agreement with the modified ABC model because these genes are expressed only in whorls 2 and 3 and not in whorl 1 ( Fig. 3F; Park et al, 2003Park et al, , 2004. However, an asparagus floral homeotic mutant with two whorls of sepaloid tepals in whorls 1 and 2 and stamens transformed to carpels in whorl 3 has been identified ( Fig.…”
Section: -2) Lily-type Flowers-a Perianth With Two Petaloid Whorlsmentioning
confidence: 99%
“…In situ hybridization analyses revealed the presence of mRNAs of class B genes in the primordia of the outer tepals in Agapanthus praecox (Nakamura et al 2005) and Alstroemeria ligtu (Hirai et al 2007). However, expression of these genes was not detected in the primordia of the outer tepals in Asparagus officinalis (Park et al 2003(Park et al , 2004. In addition, there is another type of genes that is important for eudicots sepal and petal identities, class A SQUAMOSA (SQ)-like genes, named after A. majus gene.…”
Section: Introductionmentioning
confidence: 99%
“…The development of male and female asparagus flowers has been investigated in detail by scanning electron microscopy (Caporali et al 1994) and the floral homeotic genes, based on the ABCDE model, have been isolated and characterized (Caporali et al 2000, Park et al 2003, Losa et al 2004, Park et al 2004, Ito et al 2005. The sex determination system of garden asparagus is known to depend on so-called sex chromosomes and genetic experiments demonstrated that females are homogametic (XX) while males are heterogametic (XY) (Kappert 1941, Marziani et al 1999, Uno et al 2002.…”
mentioning
confidence: 99%